Prevalence and Determinants of Healthy Aging Among Older Adults in Jining, China - Yusuf, Tang Linxi, Azlina; Rasudin, Nur Syahmina Binti (Science, Technology, and Social Sciences Procedia, 2025)
Population aging in China is accelerating rapidly, making the promotion of healthy aging a critical public health and nursing priority. This cross-sectional study, conducted in Jining City, Shandong Province, aimed to examine the prevalence and determinants of healthy aging among older adults and to provide empirical evidence for the design of targeted nursing and community-based interventions. From October 2024 to January 2025, a multi-stage random sampling method was employed to recruit 806 older adults aged 60 years and above from both urban and rural communities. Data were collected using a self-designed sociodemographic questionnaire, the Healthy Aging Questionnaire (HAQ), and the Simplified Chinese Version of the Health-Promoting Behaviours Scale for the Elderly, and were analyzed with SPSS version 27.0. Descriptive statistics, one-way ANOVA, and multiple linear regression analyses were performed to identify predictors of healthy aging. The mean healthy aging score was 50.21 ± 15.52, with only 13.5% of participants achieving a high level of healthy aging. Regression analysis revealed eleven significant predictors (p < 0.05), including age, gender, residence, marital status, family relationships, contact with children, education, income, chronic disease status, self-rated health, and health-promoting behaviours. Older adults who were married, urban residents, highly educated, financially secure, and actively engaged in health-promoting behaviours demonstrated better healthy aging outcomes. These findings indicate that the level of healthy aging among older adults in Jining remains relatively low. Nursing-led, community-based interventions focusing on health education, chronic disease management, psychosocial support, and family engagement are essential to enhance health-promoting behaviours and foster healthy aging among older adults in China.